Estimate of the glomerular filtration rate in aged adults through the CKD-EPI equations - Yoandri Bandera Ramos; Pablo Yulior Ge Martínez; Yanay Pérez Pérez (Centro Provincial de Información de Ciencias Médicas, 2019)
Introduction: The glomerular filtration rate is considered the best index to evaluate the renal function, since its reduction is evidenced much time before any clinical manifestation which derives from the renal failure.   Methods: A descriptive, cross-sectional and observational study of 92 patients without and with renal disease, assisted in Dr. Juan Bruno Zayas Alfonso Teaching General Hospital in Santiago de Cuba, from February to November, 2017, was carried out in order to estimate glomerular filtrate in older adults by means of the CKD-EPI equations.  Results: Lower average filtrate with 24 hours urine was found in the group without nefropathy (64.8 mL/min) and it was higher in the kidney disease group (25.8 mL/min) regarding these equations. Although in both groups there were no significant differences in the filtrate according to age, sex and corporal weight, when using the equations CKD-EPI, the higher values were obtained with CKD-EPI cystatine C.    Conclusions: The use of the formulas CKD-EPI with cystatine allows a better estimate of the renal function in aged patients without markers of renal damage.